Electromagnetic radiation level detection and monitoring system for triple band GSM signal using calculable antenna factor method - Nor Rahim, Puteri Alifah Ilyana (2018)
The project is about monitoring electromagnetic (EM) radiation level for mobile frequency range where the system is capable of detecting the level of electromagnetic radiation (in volts/meter) by the receiver antenna (sensors) at the frequencies of 0.9 GHz, 1.8 GHz and 2.1 GHz. The system then compares the detected level with the safety limits set by international standard (ICNIRP). The designed unit acts as a receiver which is a sensor, and a detector which is used to produce accurate DC voltage. The sensors are then tested with three different methods which are analytical, simulation and SAM measurement methods to determine the antenna factor (AF) which is one of the most important antenna characteristics used to determine the electric field from antenna radiation or reception. Based on the results of AF, a good agreement is observed between the analytical, simulation and measurement methods for high frequency while there is a significant different in AF result for low frequency. In addition, the AF result for all frequencies using SAM measurement is higher than analytical and simulaton methods that are 37.64 dB/m for 0.9 GHz, 38.10 dB/m for 1.8 GHz and 36.37 dB/m for 2.1 GHz. Uncertainties in the calculable AF are on average ±4.6478dB. An electric field radiation measurement is conducted near the base transceiver station in University Tun Hussein Onn Malaysia (UTHM). The electric field for the proposed system is measured and then compared with the real antenna to analyse the functionality of the sensor in order to get the £-field value. The £-field results show good agreement between the proposed system and the existing system using spectrum analyser for all the operating frequencies with the deviation of ±5.00 dBV/m. In summary, the designed sensor can be used for the proposed monitoring system and also can be further improved for receiving electromagnetic radiation from all directions by implementing triple band system for better coverage and to reduce the size of sensor.